Evaluation of biological control option for Bagrada bug (Bagrada hilaris (Burmeister)) in Kenya - Otieno, N.; Saidi, M.; Opiyo, A.; Kasina, M.; Guantai, M. (International Journal of Horticultural Science, 2024)
Brassica production is important for economic development of Kenya. Bagrada bug, a significant pest of brassicas, affects their yields and quality, currently posing a threat to both local and commercial vegetable production in Kenya. Biological control of bagrada bug using natural enemies is a cheaper and environmentally friendly method. The study aimed to identify native egg parasitoid species in Kenya. A field prospection survey of the bagrada bug egg parasitoid was done by a series of bagrada bug egg exposure in different parts of the country. Freshly laid bagrada bug eggs in cards were exposed for possible parasitism in the field for three days. The eggs were later carried to the laboratory at NSRC to await hatching. Two egg parasitoid species Trissolcus basalis (Hymenoptera, Scelionidae) and Gryon sp. were identified during the study after a period of bagrada bug egg exposure in Machakos and Kisumu. Two cards with parasitized bagrada bug eggs were recovered from Machakos from which one card yielded four parasitoids of one species Trissolcus basalis and the other yielded two parasitoids Trissolcus basalis and Gryon sp. One card with two parasitized eggs by Trissolcus basalis was recovered from Kisumu, however, there were no parasitoids identified in Nanyuki, Naivasha and Kitengela where bagrada bug is also prevalent. Results showed parasitoid presence in fields with high bug populations compared to areas with few or no Bagrada bug infestations. Conducting trials in both laboratory and field settings is recommended to obtain clear data on the effectiveness of the identified egg parasitoid in managing the bagrada bug population.